The Spectre of Deflation: A Review of Empirical Evidence - Gregor W. Smith (Queen's University, Department of Economics, 2006)
What explains the widespread fear of deflation? This paper reviews the history of thought, economic history, and empirical evidence on deflation, with a view to answering this question. It also outlines informally the main effects of deflation in applied monetary models. The main finding is that – for both historical and contemporary deflations – there are many open, empirical questions that could be answered using the tools economists use to study inflation and monetary policy more generally.
Keywords: E31; 330; deflation